MULTİPLE ASPECTS OF GRAMMAR İN THE BOOKS OF GRAMMAR OF THE HOLY QURAN - A COMPARATİVE STUDY (American Journal of Research in Humanities and Social Sciences, 2024)
This research studied the multiplicity of grammatical aspects of a single word in the Holy Quran under the title "Multiplicity of grammatical aspects in the books of grammar of the Holy Quran" A comparative study, and the research showed the differences in the multiple grammatical aspects that occur in a non-grammatical chapter, and dealt with the presentation and analysis of the most important opinions, and the reason for these differences that occurred between grammarians, and also studied the methods that can be relied upon to overcome these differences, and the way to prefer one opinion over another, and how we can classify the grammatical chapter of the word in which the disagreement occurred. The research was more interested in the meaning that the grammatical movement conveys than in the grammatical movement itself.It became clear to me that some of these classifications - the books of grammar of the Holy Quran - were copying from their predecessors, and some of them were satisfied with merely mentioning these grammatical aspects without preferring one aspect over another, while a third group came with the multiple aspects and discussed them in a discussion that reflects a rare mentality, and in general, the grammarians of Arabic proved that they are truly the guardians of the sciences of language and grammar and that they came with what no one else came with, as they applied reason in Their opinions, and they excelled in graduating their issues